Improving bone health in men with prostate cancer receiving androgen deprivation therapy: Results of a randomized phase 2 trial. Issue 6 (6th December 2017) - Alibhai, Shabbir M.H.; Breunis, Henriette; Timilshina, Narhari; Hamidi, Maryam S.; Cheung, Angela M.; Tomlinson, George A.; Manokumar, Tharsika; Samadi, Osai; Sandoval, Joanna; Durbano, Sara; Warde, Padraig; Jones, Jennifer M.
Abstract : BACKGROUND: Strategies to improve bone health care in men receiving androgen deprivation therapy (ADT) are not consistently implemented. The authors conducted a phase 2 randomized controlled trial of 2 education‐based models‐of‐care interventions to determine their feasibility and ability to improve bone health care. METHODS: A single‐center parallel‐group randomized controlled trial of men with prostate cancer who were receiving ADT was performed. Participants were randomized 1:1:1 to 1) a patient bone health pamphlet and brief recommendations for their family physician (BHP+FP); 2) a BHP and support from a bone health care coordinator (BHP+BHCC); or 3) usual care. The primary efficacy outcome was receipt of a bone mineral density (BMD) test within 6 months. Secondary efficacy outcomes included guideline‐appropriate calcium and vitamin D use and bisphosphonate prescriptions for men at high fracture risk. Feasibility endpoints included recruitment, retention, satisfaction, contamination, and outcome capture. The main analysis used logistic regression with a 1‐sided P of .10. The trial is registered atClinicalTrials.gov (identifier NCT02043236). RESULTS: A total of 119 men were recruited. The BHP+BHCC strategy was associated with a greater percentage of men undergoing a BMD test compared with the usual‐care group (78% vs 36%; P <.001). BMD ordering also was found to be increased with the BHP+FP strategy (58% vs 36%; P = .047). Both strategies were associated with higher percentages of patients using calcium and vitamin D, but only the BHP+FP arm was statistically significant ( P = .039). No men were detected to be at high fracture risk. All but one feasibility endpoint was met. CONCLUSIONS: Educational strategies to improve bone health care appear feasible and are associated with improved BMD ordering in men receiving ADT. Cancer 2018;124:1132‐40. © 2017 American Cancer Society . Abstract : This phase 2 trial demonstrates the feasibility and efficacy of 2 educational interventions to improve bone mineral density test ordering and calcium and vitamin D use in men receiving androgen deprivation therapy for prostate cancer. A larger trial is needed to confirm the results.